Beetroot juice, exercise, and cardiovascular function in women planning to conceive - Osman, Mubarak M A; Mullins, Edward; Kleprlikova, Hana; Wilkinson, Ian B; Lees, Christoph (Journal of hypertension, 2024)
OBJECTIVE: Prepregnancy optimization of cardiovascular function may reduce the risk of pre-eclampsia. We aimed to assess the feasibility and effect of preconception cardiovascular monitoring, exercise, and beetroot juice on cardiovascular parameters in women planning to conceive. DESIGN AND METHOD: Prospective single-site, open-label, randomized controlled trial. Thirty-two women, aged 18-45 years, were allocated into one of four arms (1 : 1 : 1 : 1): exercise, beetroot juice, exercise plus beetroot juice and no intervention for 12 weeks. Blood pressure (BP) was measured at home daily. Cardiac output ( CO ) and total peripheral resistance (TPR) were assessed via bio-impedance. RESULTS: Twenty-nine out of 32 (91%) participants completed the study. Adherence to daily BP and weight measurements were 81% and 78%, respectively ( n = 29). Eight out of 15 (53%) of participants did not drink all the provided beetroot juice because of forgetfulness and taste. After 12 weeks, exercise was associated with a reduction in standing TPR (-278 ± 0.272 dynes s cm -5 , P < 0.05), and an increase in standing CO (+0.88 ± 0.71 l/min, P < 0.05). Exercise and beetroot juice together was associated with a reduction in standing DBP ( 7 ± 6 mmHg, P < 0.05), and an increase in standing CO (+0.49 ± 0.66 l/min, P < 0.05). The control group showed a reduction in standing TPR ( 313 ± 387 dynes s cm -5 ) and standing DBP ( 8 ± 5mmHg). All groups gained weight. CONCLUSION: Exercise and beetroot juice in combination showed a signal towards improving cardiovascular parameters. The control group showed improvements, indicating that home measurement devices and regular recording of parameters are interventions in themselves. Nevertheless, interventions before pregnancy to improve cardiovascular parameters may alter the occurrence of hypertensive conditions during pregnancy and require further investigation in adequately powered studies.
Keywords: Nitrates; hypertenze; Female; ženské pohlaví; Dietary Supplements; lidé; dvojitá slepá metoda; cvičení; těhotenství; potravní doplňky; krevní tlak; prospektivní studie; Hypertension; Double-Blind Method; Prospective Studies; dusičnany; Pregnancy; Blood Pressure; Exercise; Humans